Patients Rights - Srivastava, CP (Journal of Universal College of Medical Sciences, 2013)
Gone are the days when a treating doctor was treated as next to god! The education and literacy is rising day by day and so is the awareness among people of every walk of life. Human rights propagated by the United Nations is already in existence. Our children, students and people of the world today are conscious of their rights. Thus patients also are aware of their rights. This is a healthy modern trend for the medical world today. DOI: http://dx.doi.org/10.3126/jucms.v1i3.8771 Journal of Universal College of Medical Sciences Vol.1(3) 2013: 71-72